Mitochondrial Dynamics and Bioenergetic Alteration During Inflammatory Activation of Astrocytes - Rahman, Md Habibur; Suk, Kyoungho (Frontiers in Aging Neuroscience, 2020)
Mitochondria are essential cellular organelles that act as metabolic centers and signaling platforms and have been identified as an important subcellular target in a broad range of neuropathologies. Studies on the role of mitochondria in neurological disorders have primarily focused on neurons. However, dysfunctional mitochondria in glial cells, particularly astrocytes, have recently gained research attention due to their close involvement in neuroinflammation and metabolic and neurodegenerative disorders. Furthermore, alterations in mitochondrial energy metabolism in astrocytes have been reported to modulate cellular morphology and activity and induce the release of diverse proinflammatory mediators. Moreover, emerging evidence suggests that dysregulation of mitochondrial dynamics characterized by aberrant fission and fusion events in glial cells is closely associated with the inflammatory activation of glia. In this mini-review, we cover the recent advances in the molecular aspects of astrocytic mitochondrial dynamics and their metabolic changes under the pathological conditions of the central nervous system.